Subsurfaces Modeling Based on Integrated Geophysics Method to Identify Mineralization Zone In "X" Area, West Java, Indonesia - Yuliwardana, Arditiya Tri; Yatini, Yatini (Aceh International Journal of Science and Technology, 2024)
Ring of fire passes through Indonesia, causing the presence of abundant mineral resource potential. Potential minerals in Indonesia are formed by hydrothermal processes. One of the hydrothermal deposits is a high-sulfidation epithermal (HSE) deposit. The appropriate geophysical methods can be used to find potential mineral resources. The geomagnetic method can detect mineralization by analyzing the development of structural pattern control. Tilt derivative filters used in magnetic data can clarify anomalous boundaries, especially structural straightness boundaries. The analysis showed that the mineralized zone had a distribution of low susceptibility values of 0.0054 to -0.0178cgs. due to destructive magnetite minerals in the advanced argillic alteration zone. Tilt derivative analysis shows the shape of a low circular anomalous pattern that extends north-south towards the boundary of the left horizontal fault, which develops into a faulty fault complex as control of mineralization. The method integration produces an HSE precipitate conceptual model, in which the presence of alteration and mineralization is controlled by a left horizontal fault zone that forms a fault complex descending in it and develops into a northwest-southeast tension vein plating dipping opening as estimation of mineralized pathways in the "X" Region, West Java, Indonesia.